(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Epithelial cells have evolved a variety of cell-and tissue-specific mechanisms for bacterial detection to enable cells to modulate the inflammatory response depending on the particular situation in a specific organ. These mechanisms provide a means of maintaining a proper balance between defense, tissue injury and their combined effects on organ function, and the molecule CD14 may have a role to play. Objective: to find any correlation between CD14 marker expression and bladder cancer. Material and methods: The immunoexpression of CD14 in paraffin sections from 96- bladder cancer tissues and 36-bladder tissues from patients with other bladder disease rather than cancer was investigated using immunohistochemical assay (IHC). The patients were divided into three groups: Group-1: Newly diagnosed bladder cancer patients, 69(43.9%), Group-2:Post-chemotherapy patients, 27(17.2%), Group-3: Other bladder disorders rather than bladder cancer 36(22.9%). The final diagnosis of patients with bladder cancer was established by clinical examination confirmed by cystoscopy and histopathological examination for bladder tissue specimens. Urinary tract infections were studied for all groups by culturing urine samples using specific culture media. Results: The results showed that CD14 protein was over expressed in 68.57% of the patients with approximately equal frequent IHC score among patients(23.8%) for each of weak and intense immunoreactions, and (21.0%) for moderate one , and there was no significant difference in the scores of positive IHC CD14 expression in bladder tissue of the cancer patients when compared with non-cancer patients, but there was significant difference between cancerous patients in correlation to the tumor grades. Positive urine cultures were detected in 28(40.6%) of group-1, 13(48.1%) of group-2, and 12(33.3%) of group-3, while all healthy subjects were free of infection, and a significant difference between bacterial infected patients with and without bladder cancer, in which there was highly CD14 immunoexpression in bladder tissue in Gram-negative bacterial infected patients . Conclusion: CD14 expression correlated significantly with Gram-negative bacterial infection, but not with cancer. Key words: Immunohistochemistry, CD14, bladder cancer